Analysis and Application of Particle Backtracking Algorithm in Wind–Sand Two-Phase Flow Using SPH Method - Gao, Wenxiu; Jin, Afang; An, Zhenguo; Yan, Ming (Applied sciences, 2024)
Due to the high sensitivity of grid-based micro-scale wind–sand flow models to deformation and distortion, this study employs the Smooth Particle Hydrodynamics (SPH) method for numerical simulations. The advantage of the SPH method is that it can dynamically analyze the entire trajectory of the particles, thus allowing the initial positional distribution of sand-buried particles to be traced. This study utilizes the advantages of the SPH method. It develops particle backtracking algorithms based on the SPH method using the C language. It analyses the initial location distribution, concentration, velocity, and particle size distribution of sand-buried particles to formulate targeted measures to cope with wind–sand disasters. Meanwhile, this paper improves a particle modeling algorithm to realize arbitrary mixing particle size and mixing ratio by programming in C language and combining it with pixel recognition technology. In addition, this paper will use the particle backtracking algorithm to analyze the classical embankment wind and sand flow field and then propose adequate measures for embankment wind and sand disaster management by investigating sand particle movement characteristics.